Pengembangan Usaha Jasa Penatu (Laundry) Untuk Meningkatkan Layanan dan Nilai Tambah Ekonomi di TEFA Perhotelan Terpadu Politeknik Negeri Jember - Utami, Lely Dian; Milawaty, Milawaty; NH, Uystka Hikmatul Kamiliyah; Dzulkifli, Muhammad (P3M Politeknik Negeri Jember, 2025)
This community service activity aims to develop a laundry service business as an effort to improve services and economic added value at the TEFA Integrated Hotel of Politeknik Negeri Jember. The development of a laundry service business is considered very important because Politeknik Negeri Jember or Polije is a vocational university with BLU (Public Service Agency) status where Polije must provide services to the community in the form of providing goods and / or services that are sold without prioritizing profit and in carrying out its activities based on the principles of efficiency and productivity. This business development is expected to make a significant contribution to the quality of service at the TEFA Integrated Hotel Polije and can improve the economic welfare of business actors and the surrounding community. Methods for implementing this community service activity include three stages, namely the planning, the implementation, and the evaluation stages. These three stages were detailed more into the stage of needs analysis, the implementation of visits to laundry services, the provision of tools and the latest technology in laundry services, as well as evaluation. Additionally, this community service activity also included assistance in terms of business management, marketing, and effective customer service. Based on the implementation of this community service activity, it is expected that the laundry service business at the TEFA Integrated Hotel Polije will experience an improvement in service quality and better economic benefits, which in turn will have a positive impact toward the campus community and its surroundings.